Pemanfaatan Model Kano Dalam Mengidentifikasi Kebutuhan Utama Pengguna pada Aplikasi RIOT:ID - Sihotang, Jay Idoan (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2024)
User needs for applications considering rapid technological advancements present unique challenges. In this context, the KANO method is employed to provide an overview of the required features and to depict user perception of needs and satisfaction levels. The application designed for the RIOT Indonesia running community offers 10 attributes/features: Attractive UI, Easy to Use, Informative, Data Security, App Performance, Notification Feature, Attendance Feature, Gamification Feature, Strava Integration, and Calendar of Activities. The distributed questionnaire is expected to yield results that map out each feature. In conclusion, this study successfully captured respondents’ perceptions of feature requirements for the RIOT:ID application. Responses from participants helped categorize each feature, revealing that Data Security is a high-importance, One-dimensional feature, although it has a lower impact on satisfaction. Seven features, including Attractive UI, Ease of Use, and Strava Integration, fall under the Attractive category, indicating their significance and potential to enhance satisfaction. Conversely, Notification and Gamification features have minimal influence on user satisfaction.